A comparative analysis of the progress of e-learning education of nursing students in the field of Reliability in scientific research. E-learning education - Panczyk, Mariusz; Woynarowska-Sołdan, Magdalena; Belowska, Jarosława; Zarzeka, Aleksander; Gotlib, Joanna (Nursing in the 21st Century, 2015)
A COMPARATIVE ANALYSIS OF THE PROGRESS OF E-LEARNING EDUCATION OF NURSING STUDENTS IN THE FIELD OF RELIABILITY IN SCIENTIFIC RESEARCH. E-LEARNING EDUCATION Aim. A comparative analysis of two methods of organising e-courses designed for students of nursing and conducted throughout 2012/13 and 2013/14 at the Medical University of Warsaw (MUW) within the framework of education in “Reliability in scientific research”. Material and Methodology. A group of 285 students of the 1st degree course at the Nursing Faculty, including 141 subjects from the academic year 2012/13 and 144 from 2013/14. Data from reliability reports were analysed comparatively as well as the scored results that represented the assessment results for the solved tasks prepared in the form of Short Answer Questions (SAQs) or tests generated automatically (Multiple-Choice Questions, MCQs). Results. Students who passed the e-course in SAQ format, spent a considerable longer amount of time on the MoodleTM platform (229.1 ± 122.23 minutes, academic year of 2012/13) than the students who passed the e-course taking MCQs (175.3 ± 93.38 minutes, academic year 2013/14) (U Mann-Whitney test = 7298.0, P = 0.0002). Moreover, the activities of students in consecutive months of the academic year 2012/13 were similar to the activities of the academic year 2013/14. Reliability evaluation of the pool of test questions points to a high degree of internal consistency of the exam set (α-Cronbach = 0.93, standard error = 0.12). Conclusion. Applying an MCQ e-test ensured a reliable evaluation of the students’ progress. The final MCQ type of the test with the set time limit increases the reliability of educational measurement. Regardless of the applied system of organising e-courses, lack of systematic work on part of the students presented the greatest problem throughout the whole term.